Reflexive moralization: The crucial role of clinician moral well-being - Whitney, Clare (Nursing ethics, 2025)
BackgroundMoralization, or the application of moral value onto individuals’ actions or identities, has broad impact in the context of health and healthcare. In particular, moralization may result in interpersonal and institutional consequences for certain groups of individuals such as people who use substances during pregnancy or while feeding human milk. Reflexive moralization is an underexplored phenomenon that represents the reflex-like nature of some instances of moralization. Objectives: The purpose of this study was to explore and explain how reflexive moralization impacts the perinatal care of substance-exposed dyads.Research DesignIn this targeted sub-analysis, dimensional analysis was used in the mode of emergent fit to analyze qualitative interviews conducted for a parent study investigating the circumstances under which clinicians bring moral considerations into the care of substance-exposed dyads.Participants and Research ContextInterviews with fifteen perinatal health clinician providing health or social care to substance-exposed dyads were included in this analysis.Ethical ConsiderationsThe X IRB determined this study exempt. All participants provided informed consent prior to enrolling in the study.ResultsFindings revealed novel dimensions of reflexive moralization, including the process of sympathization, which occurs when clinicians demoralize and transform their reflexive moralization into a tool for care. In order for the transformative process of sympathization to occur, clinician moral well-being must be assessed as sufficient, meaning clinicians must feel they have the capacity and competence to provide adequate care to patients. Discussion: Future research should further investigate the nature of clinician moral well-being in order to measure and develop interventions to support it.ConclusionsClinician moral well-being plays a pivotal role in clinical care delivery for substance-exposed dyads, in the context of reflexive moralization.